Pengaruh Potongan Harga, Citra Merek Dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Paket Umrah Pada PT. Safara Layanan Utama Kecamatan Krejengan Kabupaten Probolinggo - Kamal, Muhammad Alfin; Haris, R Abdul; Pujiastuti, Agustina (Universitas Panca Marga, 2024)
The aim of this research is to determine the partial influence of price discounts, brand image and consumer trust on purchasing decisions at PT. Safara Main Service Kec. Krejengan, Probolinggo Regency. The type of research used is quantitative with an associative approach. The population in this research is consumers of PT. Safara Main Service Kec. Krejengan, Probolinggo Regency in the period January – December 2023. The number of samples in this study was 90, obtained from calculating the Slovin formula. In proving and analyzing this, validity and reliability tests, classical assumption tests, multiple linear analysis, R2 coefficient of determination analysis, Hepotesis test are used. The research results show that price discounts (X1), brand image (X2) and consumer trust (X3) have a partial and significant effect on purchasing decisions (Y).